Health Related Quality of Life among the Coronary Heart Disease Patients - Mandal, Sabita; Ghosh, Shantonu Kumar; Rahman, Mahbubur; Majumder, Alpana; Ranjan, Redoy; Adhikary, Dipannita; Hasan, Kamrul; Islam, Md Ziaul; Adhikary, Asit Baran (Cardiovascular Journal, 2016)
Background: Coronary heart disease (CHD) is one of the leading causes of death in both developed and developing countries including Bangladesh. CHD endanger not only physical health but also psychological, environmental and social health of the patients seriously and many of them live without hope to improve. Thus evaluation of health related quality of life of such patients is very important. Methods: This descriptive cross sectional study was conducted among 217 CHD patients at the National Institute of Cardiovascular Diseases (NICVD), Sher-e-Bangla Nagar, Dhaka, during the period from January to December 2013. The study intended to assess their health related quality of life in terms of general health, physical health, psychological health, social relationship and environmental conditions. Data were collected by a semi-structured questionnaire based on WHOQOLBREF (26) scale. Results: Regarding level of quality of life and general health, majority (51.2%) had average quality of life while in respect of physical health, most (89.9%) of the patients had average quality of health. Regarding psychological health, majority (72.8%) had average quality while regarding social relationship, majority (53.9%) had average quality and by environmental conditions, majority (64.1%) had average quality. Overall health related quality of life by age of the CHD patients was statistically significant as most (391.3%) of the CHD patients with age 30-49 years had average while majority (53.3%) of the elderly (65-75 years) had poor quality of life [c2(4)=28.42, p<0.01]. Overall quality of life and general health was average among most (31.3%) of the middle aged patients while it was poor among majority (53.3%) of the elderly patients and this variation was statistically significant [c2(10)=35.89, p<0.01]. Overall quality of life and general health was average among most (91.3%) of the middle aged patients while it was poor among majority (53.3%) of the elderly patients and this variation was statistically significant (c2(4), p<0.01). All of the retired patients had average and most (94.0%) of the service-holder had average physical health. Conclusion: The study recommends effective measures to improve the overall health related quality of life of the CHD patients in the context of Bangladesh. Cardiovasc. j. 2016; 9(1): 43-48